Integrating Problem-Solving Skills in Developing Trigonometric Ratio Learning Videos for Right-Angled Triangles - Kikin Novia Riskadewi (The Indonesian Institute of Science and Technology Research, 2023)
There is a need for innovative instructional media that incorporates technology to facilitate teaching for educators and enhance learning for students. This study aims to develop a valid and practical instructional video using the Renderforest application and the Discovery Learning method, integrated with mathematical problem-solving skills in teaching trigonometric ratios in right-angled triangles. The research follows a development approach focusing on mathematics instructional videos. The research and development methodology is based on product development steps. The product's feasibility is measured through validation and practicality testing. Data collection techniques include interviews, questionnaires, and surveys. Based on the research findings, the instructional video's validity was evaluated by experts, with a feasibility score of 78%, indicating its validity. Additionally, the media experts deemed it 80% feasible. The practicality test yielded a score of 80%, marking its practicality. Therefore, the developed instructional video using the Renderforest application and the Discovery Learning method, integrated with mathematical problem-solving skills in teaching trigonometric ratios in right-angled triangles, is considered valid and practical.